Penerapan Brain Gym Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPS Kelas V SD - Refi Damayanti; M Hosnan; Ujang Jamaludin (Universitas Negeri Makassar, 2020)
This study aims to determine the application of the Brain Gym in improving student learning outcomes in social studies lessons in class V. The research was conducted at SDN Kebaharan 1, Serang City 2019/2020. This research method uses a quasi-experimental Nonequivalent Control Grop Design. The population studied was grade V SD students. The sample was taken by using the purposive sampling technique. This research uses to test and non-test instruments. The tests are in the form of a pretest and posttest. Based on pretest data processing, it was obtained that the average value of learning outcomes in social studies subjects in the control class was 40.71% in the experimental class of 32.20%. Thus the learning outcomes of students before being given treatment were not different. After being given the treatment and given the posttest, based on data processing, the average value of student learning outcomes in the control class was 72.90% and the experimental class was 80.46%. After being treated the experimental class learning outcomes were better than the control class. Based on the research results it can be concluded that the application of the Brain Gym can improve the social studies learning outcomes of students in class V SD.